Catalyst design based on microkinetic models: Oxidative coupling of methane - Thybaut, Joris W.; Sun, Jianjun; Olivier, Louis; Van Veen, André C.; Mirodatos, Claude; Marin, Guy B. (Catalysis today, 2011)
An extended microkinetic model for methane oxidative coupling (OCM) including so-called catalyst descriptors has been used for the simulation of experimental data on various catalysts in different setups. The good agreement between experimental data and calculated results over a large range of operating conditions proves the capability of the model being incorporated in a high throughput workflow for OCM catalyst development. The model allows the selection of the optimal operating conditions for catalyst evaluation. The effects of operating conditions and catalyst texture properties such as feed flow rate, temperature, pressure and porosity, BET-surface area, and tortuosity, have been investigated using the model. By varying the value of catalyst descriptors, C 2 product yields have been calculated to show the effects of these descriptors on the catalytic chemistry. With this microkinetic model the yield of methane oxidative coupling products was optimized using a genetic algorithm followed by the Rosenbrock and the Levenberg–Marquardt method. The optimized parameters include catalyst descriptors, operating conditions and catalyst texture properties. Results show that even with optimal surface chemistry and operating conditions, limits exist on the attainable yield. Nevertheless, these limits were found to be beyond the yields obtained with state of the art OCM catalysts, which opens up perspectives for further catalyst improvement.